MXene-based electrochemical sensors for detection of environmental pollutants: A comprehensive review. (March 2022) - Rhouati, Amina; Berkani, Mohammed; Vasseghian, Yasser; Golzadeh, Nasrin
Abstract: Since the discovery of MXenes at Drexel University in the United States in 2011, there has been extensive research regarding various applications of MXenes including environmental remediation. MXenes with a general formula of Mn+1 Xn Tx are a class of two-dimensional (2D) transition metal carbides, carbonitrides, and nitrides with unique chemical and physical characteristics as nanomaterials. MXenes feature characteristics such as high conductivity, hydrophobicity, and large specific surface areas that are attracting attention from researchers in many fields including environmental water engineering such as desalination and wastewater treatment as well as designing and building efficient sensors to detect hazardous pollutants in water. In this study, we review recent developments in MXene-based nanocomposites for electrochemical (bio) sensing with a particular focus on the detection of hazardous pollutants, such as organic components, pesticides, nitrite, and heavy metals. Integration of these 2D materials in electrochemical enzyme-based and affinity-based biosensors for environmental pollutants is also discussed. In addition, a summary of the key challenges and future remarks are presented. Although this field is relatively new, future research on biosensors of MXene-based nanocomposites need to exploit the remarkable properties of these 2D materials. Graphical abstract: Image 1 Highlights: Application of MXenes as electrochemical sensors was presented. Synthesize procedures of MXene-based electrochemical sensors were reviewed. The efficiency of MXenes in hazardous pollutants detection was appraised. Present challenges and the future outlook of MXenes in pollutants sensing were emphasized.